Modelling of solid waste incineration - Normah Abdullah; Rakmi Abdul Rahman; Razali Deman (1996)
A model for incineration of municipal solid wastes was formulated based on material and energy balances and reaction kinetics. The model was tested for various air supply rates. The study has given a picture of variations in the incineration chambers. The simulations has also shown that the slowest stages in the incineration process is the initial feed heating and the water vapourisation